2023
DOI: 10.3389/fmicb.2023.1218152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiota and untargeted gut tissue metabolome of Chinese mitten crabs (Eriocheir sinensis) with different shell colors

Abstract: IntroductionThe Chinese mitten crab (Eriocheir sinensis) is a highly valued freshwater crustacean in China. While the natural shell color of E. sinensis is greenish brown (GH), we found a variety with a brownish-orange shell color (RH). Although RH is more expensive, it exhibits a lower molting frequency and growth rate compared with GH, which significantly reduces its yield and hinders large-scale farming. The growth and development of animals are closely related to their gut microbiota and gut tissue metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Here, the dominant species of the gut microbiota belonged to the phylum of Proteobacteria , Actinobacteria , and Bacteroidetes , which is similar to the results of previous studies. For example, Zhu et al found that these three phyla were dominant in gut of adult Eriocheir sinensis [ 44 ]. Bacteria from different phyla usually show differences in maintaining important intestinal functions and homeostasis, thus changes in their relative abundance may not only indicate changes in the external environment, but also characterize differences in host gene expression as well as developmental processes [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the dominant species of the gut microbiota belonged to the phylum of Proteobacteria , Actinobacteria , and Bacteroidetes , which is similar to the results of previous studies. For example, Zhu et al found that these three phyla were dominant in gut of adult Eriocheir sinensis [ 44 ]. Bacteria from different phyla usually show differences in maintaining important intestinal functions and homeostasis, thus changes in their relative abundance may not only indicate changes in the external environment, but also characterize differences in host gene expression as well as developmental processes [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…mostly exhibits an arsenal of compounds which enable it to bind gastric epithelial cells. CagA, VacA, adhesins, and lipopolysaccharides (LPSs) or endotoxins are major molecules able to cause an inflammatory status of the gastric mucosa, which may transit to a neoplastic condition, such as gastric carcinoma [11]. It is noteworthy that the LPS of H.p.…”
Section: Introductionmentioning
confidence: 99%